The Urgency of Regulating Remote Working System In Indonesia Between Certainty and Utility - Kristanti, Brigita Estu Putri; Sihabudin; Hamidah, Siti (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2023)
The absence of comprehensive regulations regarding remote work in Indonesia has given rise to various challenges, particularly concerning justice, legal certainty, and benefits for workers. Analyzing the Implementation of Legal Protection for Parties through Agreements Offered by Authorized Officials Regarding Underhand Debt Dispute with Objects Bound by Purchase. The methodology employed in this study is normative juridical, utilizing Namely, it is carried out through an examination of legislative regulations related to the urgency of remote working regulations in Indonesia. and conceptual approaches involves reviewing the opinions of experts regarding the urgency of remote working regulations in Indonesia. The legal material analysis technique employs Grammatical interpretation, Systematic interpretation, and Teleological interpretation. The research findings indicate that, from philosophical, normative, juridical, and sociological standpoints, there is an urgent need to tailor regulations that can address the unique aspects of remote work, which fundamentally differ from conventional office-based employment.